STRATEGIC ANALYSIS OF THE EXTERNAL ENVIRONMENT OF THE CONSTRUCTION INDUSTRY OF UKRAINE - Ажаман, Ірина; Гордєєв, Олексій; Петрищенко, Наталія (Journal of Strategic Economic Research, 2022)
Dynamic changes in the environment require modern enterprises to develop and implement a set of measures for their continuous monitoring in order to create conditions for rapid, flexible response and adaptation of the organization. This will maintain the company's position in the market and help increase its competitiveness, efficiency of production and economic activities and achieve strategic goals. To solve this problem, it is important to use modern tools for environmental research. In addition, such tools should be adapted to the characteristics of the enterprise, take into account its scope, size, leadership style and more. Accordingly, it is important to study the practical aspects of using the tools of strategic analysis of the environment of the construction industry. Examining the set of methods of environmental analysis for the company under consideration, the method of PEST-analysis was chosen, which allows to assess the main factors of the macro environment that affect the business activities of the construction industry – political, economic, social and technological. According to the results of the study of the external environment, it was determined that the processes of improving the legal and regulatory framework are underway, which is reflected in the processes of updating the legislation in the direction of its harmonization with European values and norms. The state policy is friendly to the development of business by foreign counterparties, but aimed at supporting the national producer. The study of a group of socio-cultural factors revealed negative processes of annual population decline. Regarding the cultural component – there is a strengthening of identification of the value of their own culture, preservation of national customs and traditions, to development. Manifestation of personality, etc. The study of technological factors revealed that the main source of funding for research and development in the field of construction is private investment of legal entities and individuals, as well as investment by foreign investors. In general, the dynamics of the state of economic development of the construction industry was assessed using indicators of economic sentiment, which in 2021 was characterized by an upward trend. Summarizing the results of the PEST analysis, the predominance of hazards in terms of environmental impact on the enterprise was determined. Thus, in particular, the most significant are such dangers as rising inflation, energy prices, increased competition in the domestic market. Among the most important opportunities are the development of technology and the emergence of new materials and rising incomes, which could potentially affect the development of the construction market. Taking into account the impact of the external environment in shaping the development strategy of the enterprise is an integral part, which will predict the efficient use of company resources in the future and contribute to its adaptability and flexibility to change in the environment.